Next : the road to the good society - Etzioni, Amitai (New York, 2001)
The last eight years have seen the ascendancy of the political center in American politics.While applauding this move away from the extremes of both left and right, Amitai Etzioni argues that we still lack a clearly articulated political agenda for the next decade. With both presidential candidates staking their claim to the hallowed buy hollow center, the major parties are failing to address in any meaningful way our pressing domestic issues, including gun control, comprehensive health care, and poverty. Equal parts diagnosis and manifesto, Next issues a bracing call for greater political and community involvement. Arguing that our world-leading economy offers more opportunities that ever to end scarcity and break out of the cycle of materialism, Etzioni reacquaints the reader with the social, cultural, and spiritual values that must guide our approach to public policy questions. Making a strong case for the need for a "moderate counterculture" to temper the excesses of our stock market-obsessed society, Etzioni outlines a novel domestic agenda for tackling the principal challenges facing us in the decade to come.
Keywords: United states-Social conditions-1980